DIRECTIONS OF IMPLEMENTING CORPORATE SOCIAL RESPONSIBILITY IN UKRAINIAN ENTERPRISES - Максим Єрмаков; Олена Паливода (Економіка та суспільство)
The article analyses the current trends and forms of corporate social responsibility implementation by Ukrainian enterprises in the context of war. The study covers a lot of companies from seven key sectors of the economy, including banking, IT, agriculture, pharmaceuticals, food industry, metallurgy, and logistics. It was found that the highest level of CSR transparency and consistency is demonstrated by banks, IT companies, and agricultural enterprises that implement international standards such as GRI, ESG, and SDG. The main initiatives in the field of philanthropy, labour practices, environmental protection, customer relations, and corporate governance are identified. The problems of fragmented reporting, the declarative nature of policies in several industries, and the low level of due diligence practices are highlighted. Recommendations for strengthening CSR in the post-war economy of Ukraine through the integration of international standards and systemic support for sustainable development are formulated.